Lack of Correlation Between Intracranial Carotid Artery Modified Woodcock Calcification Score and Prognosis of Patients With Acute Ischemic Stroke After Intravenous Thrombolysis - He, Xin-Wei; Zhao, Rong; Li, Ge-Fei; Zheng, Bo; Wu, Yi-Lan; Shi, Yan-Hui; Liu, Yi-Sheng; Zhuang, Mei-Ting; Yin, Jia-Wen; Cui, Guo-Hong; Liu, Jian-Ren (Frontiers in Neurology, 2019)
There have been few studies about the association between intracranial carotid artery calcification (ICAC) and acute ischemic stroke (AIS) prognosis after intravenous thrombolysis (IVT). We aimed to analyze the association between ICAC and prognosis (including symptomatic intracranial hemorrhage (sICH), functional outcome and death) of AIS patients treated with IVT. In this retrospective study, we consecutively included 232 AIS patients treated with IVT between April 2012 and December 2018. ICAC was evaluated using the modified Woodcock calcification visual score on non-enhanced cranial computed tomography scans. Poor functional outcome was defined as a modified Rankin Scale score > 2 at 3 months. We found that the modified Woodcock calcification score was associated with ICH, poor outcome, and death in univariable analyses on the symptomatic side and/or bilaterally. However, after adjustment for other different covariates, the results showed no significant difference. We documented that the presence and severity of ICAC did not significantly modify the beneficial effects of rtPA treatment in AIS.